Applying User Centered Design and System Usability Scale to Design Knowledge Management System for Exam Proctors in Higher Education - Shabrina Salsabila Kurniawan; Nandhita Zefania Maharani; Dana Indra Sensuse; Erisva Hakiki Purwaningsih; Deden Sumirat Hidayat (Scientific Journal of Informatics, 2024)
Purpose: This research aims to develop a system interface design solution to address the university’s knowledge management problem with exam proctors. Developing a knowledge management system is expected to maintain the integrity of examinees and reduce the risk of plagiarism. This research identifies user needs in business processes and maps them to relevant features based on previous research. Methods: This research adopted a user-centered design methodology in developing interface design solutions, which consisted of four stages: understanding the context of use, specifying user requirements, designing solutions, and evaluating against requirements. Semi-structured interviews were used for data collection, and a system usability scale (SUS) questionnaire was employed for design solution evaluation. Result: This research identified the needs of business processes in higher education in the context of exam proctors and mapped them to a suitable feature solution. Recommendations for information architecture and knowledge management system design implementation in higher education were also provided. This research achieved a SUS score of 74.8, indicating that the developed system met users’ needs. Novelty: This research provides a practical implementation of developing a knowledge management system in higher education with user-centered design.